1993
DOI: 10.1111/j.1365-2265.1993.tb02144.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of LH and insulin resistance in lean and obese polycystic ovary syndrome

Abstract: PCOS was associated with a significant decrease of insulin sensitivity, independent of obesity. The correlation between LH and insulin sensitivity suggests a complementary action in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 35 publications
2
24
0
5
Order By: Relevance
“…Interestingly, our study is also the first to show an association between VDR TaqI "CC" genotype and serum levels of LH. The molecular mechanism through which this polymorphism influences LH levels is not known at present; however, previous studies have shown significant associations between VDR gene variants and insulin resistance on one side [18], and insulin resistance and LH on the other [19]. Furthermore, it has been suggested a modulating role of 1, 25(OH) 2 D in the control of FSH secretion [20].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, our study is also the first to show an association between VDR TaqI "CC" genotype and serum levels of LH. The molecular mechanism through which this polymorphism influences LH levels is not known at present; however, previous studies have shown significant associations between VDR gene variants and insulin resistance on one side [18], and insulin resistance and LH on the other [19]. Furthermore, it has been suggested a modulating role of 1, 25(OH) 2 D in the control of FSH secretion [20].…”
Section: Discussionmentioning
confidence: 98%
“…Both fasting 31,44,73,74 and glucose-stimulated 31,75 insulin concentrations are in fact significantly higher in obese than in non-obese PCOS subgroups. Accordingly, studies examining insulin sensitivity by using different methods such as the euglycemic hyperinsulinemic clamp technique, 44,75 the frequent sample intravenous glucose test (FSivGT) 31,74 and the insulin test 76 further demonstrated that obese PCOS women had significantly lower insulin sensitivity than their non-obese PCOS counterparts and, therefore, a more severe insulin-resistant state. The percentage of women affected by PCOS and obesity presenting glucose intolerance is rather high, ranging from 20 to 49%, 15 therefore substantially above the prevalence rates reported in premenopausal women in population-based studies.…”
Section: Androgen Abnormalitiesmentioning
confidence: 99%
“…그러나, 다낭성난소증후군 환자에서 이러한 부 적절한 성선자극호르몬의 분비 이상은 모든 다낭성난소증후군 환자의 공통된 특성이 아니고 약 50-60% 이하에서 존재하는 것으로 보고되 어 왔다 [6,7].…”
unclassified
“…그러나 이러한 성선자극호르몬 분비 이상이 다낭성 난소증후군 환자에서 어떠한 역할을 하는 지에 관해서는 여전히 논란 이 있다. 몇몇 연구들에서 다낭성난소증후군 환자에서 LH 및 LH/FSH 비는 체질량지수, 체중, 인슐린 저항성(insulin resistance)과 음의 상관 관계를 보인다고 보고되어 왔다 [7,[11][12][13]. 반면, 다낭성난소증후군 환 자에서 부적절한 성선자극호르몬 분비는 인슐린 저항성이나 보상성의 고인슐린혈증의 결과가 아니며 독립적이라는 보고들도 있다 [14].…”
unclassified